DEVELOPING HIGHER-ORDER THINKING SKILLS READING COMPREHENSION QUESTIONS FOR SENIOR HIGH SCHOOL STUDENTS - Faisal Novian Hermansah; Agnes Santi Widiati (Widya Mandala Surabaya Catholic University, 2022)
This developmental research aims at developing Higher-Order Thinking Skills (HOTS) reading comprehension questions for senior high school students. This is in line with the national educational goal which is to increase the national competitiveness in the global era while manipulating Higher-Oder Thinking Skills (HOTS) in the global communication. This research is supported by the theory that HOTS questions enable students to think critically. The ADDIE model of instructional design is applied in the process of creating the HOTS reading comprehension questions. Two authentic analytical exposition texts and two authentic explanation texts are used as the reading materials. Twenty five multiple-choice questions of the Analyzing, Evaluating, and Creating levels of the cognitive domain of the Revised Bloom’s Taxonomy (RBT) are developed. A blue print is used as the basis for the questions development to ensure the content validity of the questions. Fifteen students did the test and their answers were scored by the writers. K-R21 was applied to examine the reliability coefficient resulted in r=0.68. This is considered as a high reliability. It is expected that this paper would give beneficial insights for teachers and reading material developers that providing HOTS questions are important for students as reading exercises or tests and that a multiple-choice type of questions can be used. Hence, it is also recommended that other studies be conducted in the use of other types of questions at the level of HOTS to provide more variations of reading programs for students